Turbines compressors and fans - Yahya, S. M. (New Delhi : Tata McGraw Hill, 2011)
This book is a comprehensive resource on the theoretical principles, design and performance parameters, modes of operation and major functional areas of turbomachinery.new to this editionset-up of turbomachinery laboratorylist of materials used in turbomachinerypresentation of specifications of additional types of large wind turbinesaddition of recent publications to bibliographythe book would prove immensely useful for practising engineers in the areas of power generation, aerospace, ic engines as well as industrial fans, blowers and compressors. Researchers as well as advanced level mechanical and aerospace engineering students, specialising in turbomachines, fluid machinery, steam and gas turbines, and aircraft propulsion, would find the book equally helpful.
A. Foreword -- B. Preface to the fourth edition -- C. Preface to the first edition -- D. Acknowledgements -- 1. Introduction -- Turbomachines -- Turbines -- Pumps and compressors -- Fans and blowers -- Compressible flow machines -- Incompressible flow machines -- Turbine, compressor and fan stages -- Extended turbomachines -- Axial stages -- Radial stages -- Mixed flow stages -- Impulse stages -- Reaction stages -- Variable reaction stages -- Multi-stage machines -- Stage velocity triangles -- Design conditions -- Off-design conditions -- Applications -- Notation for chapter 1 -- Questions -- 2. Thermodynamics -- Basic definitions and laws -- Energy equation -- Adiabatic flow through nozzles -- Adiabatic flow through diffusers -- Work and efficiencies in turbine stages -- Work and efficiencies in compressor stages -- Notation for chapter 2 -- Solved examples -- Questions and problems -- 3. Gas turbine plants -- Open and closed circuit plants -- Gas turbine power cycles -- Improvements in the constant pressure cycle -- Aircraft gas turbine plants -- Gas turbines for surface vehicles -- Gas turbines for electric power generation -- Gas turbines in petro-chemical industries -- Gas turbines in cryogenics -- Miscellaneous applications of gas turbines -- Notation for chapter 3 -- Solved examples -- Questions and problems -- 4. Steam turbine plants -- Types of steam turbines -- Steam power cycle -- Improvements in plant efficiency -- Heat rate -- Industrial steam turbines -- Combined steam and gas turbine plants -- Nuclear steam power plants -- Notation for chapter 4 -- Solved examples -- Questions and problems -- 5. Combined cycle plants -- The basic combined cycle -- Steam generators -- Thermal efficiencies and power output -- Fuels for combined cycle plants -- Variable load operation -- Advantages and disadvantages -- Notation for chapter 5 -- Solved examples -- Question and problems -- 6. Fluid dynamics -- Basic definitions -- Equations of motion$1 (Bcartesian coordinate system -- Equations of motion$1 (Bcylindrical coordinate system -- Equations of motion$1 (Bnatural coordinate system -- Further notes on energy equation -- Isentropic flow through blade passages -- High-speed flows -- Aerofoil blades -- Energy transfer in turbomachines -- Notation for chapter 6 -- Solved examples -- Questions and problems -- 7. Dimensional analysis and performance parameters -- Units and dimensions -- Buckingham's (Ss(B-theorem -- Principle of similarity -- Incompressible flow machines -- Compressible flow machines -- Performance of turbines -- Performance of compressors -- Performance of fans and blowers -- Performance of cascades -- Notation for chapter 7 -- Solved examples -- Questions and problems -- 8. Flow through cascades -- Two-dimensional flow -- Cascade of blades -- Cascade tunnel -- Axial turbine cascade219 -- Axial compressor cascades -- Annular cascades -- Radial cascades -- Notation for chapter 8 -- Solved examples -- Questions and problems.s
Includes bibliographical references and index.
Keywords: Turbines; Compressors; Fans (Machinery)